Opportunistic salpingectomy versus traditional partial salpingectomy at the time of cesarean delivery: a non-inferiority randomized controlled trial - Rubin Raju; Enid Y. Rivera-Chiauzzi; Angela C. Thompson; Margaret L. Dow; Kyle D. Traynor; Laura L. Elliott; Marnie M. Wetzstein; Matthew A. Hathcock; Megan E. Branda; Vanessa E. Torbenson (IMR Press, 2022)
Background: Ovarian cancer has the highest mortality of all gynecologic malignancies, howeverthere is no proven effective screening for ovarian cancer. Evidence suggests that epithelial ovarian cancer begins in the fallopian tubes. Prophylactic bilateral total salpingectomy has been shown to reduce the risk of epithelial ovarian cancer and is now recommended to be considered at the time of sterilization procedures. There are limited well designed clinical trials that compare the safety and feasibility of total salpingectomy to that of traditional partial salpingectomy for tubal sterilization in obstetrics. We thus conducted a randomized controlled trial to assess the safety of bilateral total salpingectomy at the time of cesarean delivery. Methods: We conducted a non-inferiority randomized controlled trial at the Mayo Clinic, Rochester, Minnesota. Women age 21 years and older who were undergoing cesarean delivery and desired concomitant sterilization were enrolled between May 17, 2017 and July 16, 2018. Stratified randomization was performed based on number of previous cesarean deliveries and their Basal Metabolic Index, into a bilateral total salpingectomy (BTS) group and bilateral partial salpingectomy (BPS) group. All salpingectomies were performed using clamps and suture. The primary outcome was to compare the mean peri-operative hemoglobin change for both groups. Secondary objectives included sterilization completion time, postoperative length of stay, estimated blood loss, postoperative pain and adverse events. Results: Of the 111 women screened, 40 were enrolled and randomized. Of these, 38 underwent the assigned procedure (18 BTS, 20 BPS). No difference in Mean ± SD hemoglobin drop between groups (1.4 ± 0.7 g/dL for the BPS group and 1.8 ± 1.0 g/dL for the BTS group, p = 0.08), however the point estimate of -0.4 is very close to the non-inferiority margin of -0.5, and the CI widely exceeds the non-inferiority margin (95% CI -0.99, 0.17). Therefore non-inferiority was not shown. Mean time to completion of sterilization procedure was significantly longer in the BTS group (16.3 ± 5.6 minutes for the BTS group vs 5.1 ± 1.6 minutes for the BPS group, p < 0.01). No significant differences for other outcome measures. Conclusions: Bilateral total salpingectomy is not non-inferior to tradiational bilateral partial salpingectomy with regards to postoperative hemoglobin drop, and is associated with a small increase in operative time. There, however, was no difference in adverse events, postoperative length of stay and postoperative pain between the two groups. This information may be helpful when counseling patients.